Ignoratio Elenchi in the Amendment to the Regional Government Law and its Impact on the Executive Review of Governor Regulations and Gender Equity - Rizki Emil Birham; Natsir Asnawi (Ridwan Institute, 2026)
The purpose of this study is to examine the fallacy of reasoning (ignoratio elenchi) in the Law Number 23 of 2014 concerning Regional Government, as amended by Law Number 6 of 2023 concerning Job Creation, and its consequences for gender equity and the executive review process of gubernatorial regulations. This paper evaluates numerous pertinent legal provisions and doctrines using a normative juridical method using a statutory and conceptual approach. The study's findings show that the norm's modification conflicts with the ratio decidendi of Constitutional Court Decision Number 56/PUU-XIV/2016, which affirms the existence of executive review of gubernatorial regulations, thus reflecting a fallacy of reasoning in the form of ignoratio elenchi. As a result, a legal vacuum has occurred in the administrative oversight mechanism for regional head regulations, which has an impact on weakening legal certainty and opening space for the birth of regulations that conflict with higher regulations and have the potential to discriminate against women, as seen in the practice of gubernatorial regulations that change imperative norms into discretionary norms. Therefore, this study recommends legal reconstruction through strengthening the executive review mechanism, developing preventive oversight mechanisms, and integrating a gender justice perspective into the formation of laws and regulations to ensure normative consistency and protection for vulnerable groups.